2020
DOI: 10.2147/jbm.s254116
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative Anemia Screening and Treatment Practices in Patients Having Total Joint Replacement Surgery: A Retrospective, Observational Audit</p>

Abstract: Background: Surgical patients with preoperative anemia are more likely to experience adverse outcomes. Patient blood management (PBM) guidelines recommend screening and treating patients for anemia preoperatively to enable optimisation before surgery. This study investigates compliance with PBM guidelines and reports the association between length of stay and transfusion risk in patients with preoperative anemia. Study Design and Methods: A retrospective, observational, chart audit that included all patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Assuming a baseline (pre-implementation) level of compliance of 5% during sample size calculations, 400 patients (200 pre and 200 post implementation) are needed to detect a 20% absolute improvement in compliance (ie, Post-stage compliance of 25%). 31 , 32 Data will be described using means and standard deviations, for continuous variables, and counts and percentages, for categorical data. Statistical analysis for the patient outcomes (proportion of patients anemic on the day of surgery, and proportion of patients who receive a blood transfusion during the peri-operative period) will involve using binary logistic regression.…”
Section: Methods and Designmentioning
confidence: 99%
“…Assuming a baseline (pre-implementation) level of compliance of 5% during sample size calculations, 400 patients (200 pre and 200 post implementation) are needed to detect a 20% absolute improvement in compliance (ie, Post-stage compliance of 25%). 31 , 32 Data will be described using means and standard deviations, for continuous variables, and counts and percentages, for categorical data. Statistical analysis for the patient outcomes (proportion of patients anemic on the day of surgery, and proportion of patients who receive a blood transfusion during the peri-operative period) will involve using binary logistic regression.…”
Section: Methods and Designmentioning
confidence: 99%
“…Many patients do not have routine laboratory studies until a day or 2 before surgery, and even when a patient is identified as having anemia, further testing and diagnosis of cause are incomplete. 60 To avoid missing the opportunity to evaluate anemia once recognized, it is possible to draw all necessary laboratory studies at the time of initial anemia screening, and only run the additional tests if and when anemia is identified, through leveraging the electronic medical record (EMR). 61 The EMR can also be used to prompt for anemia evaluation as soon as surgery is scheduled, and in institutions that have it, we recommend leveraging the EMR to provide alerts to clinicians to identify patients who are anemic before surgery and prompt further evaluation.…”
Section: Summary Of Recommendations and Supporting Evidencementioning
confidence: 99%
“…46 The concept of managing and preserving the patient's own blood is not only empowering for patients but is also evidenced-based management that reduces the risk of receiving a blood transfusion. 9,38,[47][48][49][50] Effectively implemented PBM programs tick all the boxes of evidence, quality, safety, cost-effectiveness, and ethics, and ensure blood advocacy for patients while implementing pathways and tools that aim for optimal clinical outcomes. 51…”
Section: Patients and Their Advocatesmentioning
confidence: 99%